2006
DOI: 10.1007/s00795-006-0330-y
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructural morphology of native hepatitis B virus

Abstract: Cell lines (2.2.15 cells) capable of supporting the replication of hepatitis B virus (HBV) DNA and intact viral particles have been established by HBV DNA transfection into HepG2 cells. The purpose of this study was to determine the ultrastructural morphology of native HBV particles without purification in the culture supernatants and in sera from patients. Electron microscopy (EM) and immunogold EM of the samples were carried out using polyclonal and monoclonal anti-hepatitis B surface antigen antibodies. HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
2
8
0
3
Order By: Relevance
“…They resembled the previously described tadpole or cobra-shaped and horn-shaped particles [1,[11][12][13] . A recent report suggested that these particles are the native replicative form of HBV [13] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…They resembled the previously described tadpole or cobra-shaped and horn-shaped particles [1,[11][12][13] . A recent report suggested that these particles are the native replicative form of HBV [13] .…”
Section: Discussionsupporting
confidence: 83%
“…They resembled the previously described tadpole or cobra-shaped and horn-shaped particles [1,[11][12][13] . A recent report suggested that these particles are the native replicative form of HBV [13] . However, in agreement with this study, previous reports had shown the presence of Dane's particles connected to the vesicle membrane through either a short or a long stalk 20 nm in diameter [10,31] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In order to identify the pathway responsible for HBV‐induced collagen type I expression, we performed blocking experiments. TGF‐β1 is a potent factor in stimulating collagen type I gene transcription 11 . TGF‐β and TNF‐α response elements have been identified in the COL1A1 and COL1A2 genes 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we observed unique native HBV particles, named cobra-shaped and horn-shaped, in chronic hepatitis B patient serum without ultracentrifugation (29). These unique particles have been shown to completely disappear after ultracentrifugation.…”
Section: Discussionmentioning
confidence: 99%